Solar Harvesting: a Unique Opportunity for Organic Thermoelectrics?. Issue 45 (28th October 2019) - Jurado, José P.; Dörling, Bernhard; Zapata‐Arteaga, Osnat; Roig, Anna; Mihi, Agustín; Campoy‐Quiles, Mariano
Abstract: Thermoelectrics have emerged as a strategy for solar‐to‐electricity conversion, as they can complement photovoltaic devices as IR harvesters or operate as stand‐alone systems often under strong light and heat concentration. Inspired by the recent success of inorganic‐based solar thermoelectric generators (STEGs), in this manuscript, the potential of benchmark organic thermoelectric materials for solar harvesting is evaluated. It is shown that the inherent properties of organic semiconductors allow the possibility of fabricating organic STEGs (SOTEGs) of extraordinary simplicity. The broadband light absorption exhibited by most organic thermoelectrics combined with their low thermal conductivities results in a significant temperature rise upon illumination as seen by IR thermography. Under 2 sun illumination, a temperature difference of 50 K establishes between the illuminated and the non‐illuminated sides of a poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) film, and ≈40 K for a carbon nanotube/cellulose composite. Moreover, when using light as a heat source, the Seebeck coefficient remains unaffected, while a small photoconductivity effect is observed in PEDOT:PSS and carbon nanotubes. Then, the effect of several geometrical factors on the power output of a solar organic thermoelectric generator is investigated, enabling us to propose simple SOTEG geometries that capitalize on the planar geometry typical of solution‐processable materials. Finally, a proof‐of‐concept SOTEG is demonstrated, generating 180 nW under 2 suns. Abstract : Commonly used organic thermoelectric materials heat up significantly under illumination due to broadband light absorption and low thermal conductivities, and this heat gain can be converted into electricity via the thermoelectric effect. Harnessing the inherent properties of organic thermoelectrics and their ease of processing, this work demonstrates a solar organic thermoelectric generator (SOTEG) of extraordinary simplicity.